2021
DOI: 10.1016/j.eclinm.2021.101155
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for poor prognosis in children and adolescents with COVID-19: A systematic review and meta-analysis

Abstract: Background This study provides the first systematic review and meta-analysis to identify the predictors of unfavorable prognosis of COVID-19 in children and adolescents. Methods We searched literature databases until July 2021 for studies that investigated risk factors for unfavorable prognosis of children and adolescents with COVID-19. We used random-effects models to estimate the effect size with 95% confidence interval ( CI ). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 92 publications
3
43
0
3
Order By: Relevance
“…This study highlights that the risk of a severe COVID-19 outcome is substantially elevated for children with underlying risk factors compared with healthy children [ 8 ]. However, among paediatric COVID-19 cases with information on comorbidities, 83.7% had no reported comorbidity, demonstrating a potential population-level impact of high levels of community transmission leading to large numbers of hospital admissions among healthy children.…”
Section: Discussionmentioning
confidence: 99%
“…This study highlights that the risk of a severe COVID-19 outcome is substantially elevated for children with underlying risk factors compared with healthy children [ 8 ]. However, among paediatric COVID-19 cases with information on comorbidities, 83.7% had no reported comorbidity, demonstrating a potential population-level impact of high levels of community transmission leading to large numbers of hospital admissions among healthy children.…”
Section: Discussionmentioning
confidence: 99%
“…However, the disease course is quite different in children. Instead of displaying direct respiratory effects of the virus, severe pediatric cases tend to present with a hyperinflammatory response that is now called MIS-C. A recent meta-analysis investigating the predictive factors for poor prognosis in 79,104 pediatric patients with COVID-19 confirmed that patients with MIS-C had an increased risk for mortality (odds ratio (OR) = 58.00, 95% CI 6.39–526.79) [ 11 ]. Although initial studies reported MIS-C as a Kawasaki-like disease, it is now accepted that MIS-C may present with different phenotypes and outcomes [ 3 , 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Like adults, risk factors including type 2 diabetes, asthma, heart and pulmonary diseases, neurologic, neurodevelopmental (in particular, Down Syndrome) and neuromuscular conditions, and obesity have been found to affect the severity of the disease among children. [ 27 ]…”
Section: Children and Covid-19 Vaccinementioning
confidence: 99%